Core–Shell IrPt Nanoalloy on La/Ni–Co3O4 for High-Performance Bifunctional PEM Electrolysis with Ultralow Noble Metal Loading - Liu, Yifei; Er, Xinmeng; Wang, Xinyao; Ren, Hangxing; Wang, Wenchao; Cao, Feng; Zhang, Taiyan; Liu, Pan; Yuan, Yakun; Yu, Fangbo; Ren, Yang; Huang, Fuqiang; et al. (Nano-Micro Letters, 2025)
The development of highly efficient and durable bifunctional catalysts with minimal precious metal usage is critical for advancing proton exchange membrane water electrolysis (PEMWE). We present an iridium–platinum nanoalloy (IrPt) supported on lanthanum and nickel co-doped cobalt oxide, featuring a core–shell architecture with an amorphous IrPtOx shell and an IrPt core. This catalyst exhibits exceptional bifunctional activity for oxygen and hydrogen evolution reactions in acidic media, achieving 2 A cm−2 at 1.72 V in a PEMWE device with ultralow loadings of 0.075 mgIr cm−2 and 0.075 mgPt cm−2 at anode and cathode, respectively. It demonstrates outstanding durability, sustaining water splitting for over 646 h with a degradation rate of only 5 μV h−1, outperforming state-of-the-art Ir-based catalysts. In situ X-ray absorption spectroscopy and density functional theory simulations reveal that the optimized charge redistribution between Ir and Pt, along with the IrPt core–IrPtOx shell structure, enhances performance. The Ir–O–Pt active sites enable a bi-nuclear mechanism for oxygen evolution reaction and a Volmer–Tafel mechanism for hydrogen evolution reaction, reducing kinetic barriers. Hierarchical porosity, abundant oxygen vacancies, and a high electrochemical surface area further improve electron and mass transfer. This work offers a cost-effective solution for green hydrogen production and advances the design of high-performance bifunctional catalysts for PEMWE. Highlights: 1 Core–shell IrPt nanoalloy on La/Ni–Co₃O₄ achieves unprecedented bifunctional activity (2 A cm−2 at 1.72 V) in proton exchange membrane water electrolysis (PEMWE) with ultralow loadings (0.075 mg cm−2 Ir/Pt at both electrodes). 2 646-h durability in PEMWE cell (5 μV h−1 decay) via IrPt-core@IrPtOx-shell synergy, hierarchical pores, and oxygen vacancies for robust electron/mass transfer and active-site stability. 3 In situ X-ray absorption spectroscopy combined with density functional theory unveils Ir–O–Pt sites enabling bi-nuclear oxygen evolution reaction and Volmer–Tafel hydrogen evolution reaction mechanisms through optimized Ir/Pt charge redistribution, breaking kinetic limitations.